Berteologi Menurut Paul Ricoeur: Sebuah Sumbangan Metodologis - John C. Simon (Jurnal Teologi (Journal of Theology), 2017)
"He who is unable to reinterpret his past may also be incapable of projecting concretely his interest in emancipation" (Paul Ricoeur). In understanding a theologizing process, our attention should not focus on reality alone, but also on the means or tools to understand that reality. This paper intends to explain the means or tools of the theologizing process according to Ricoeur that is used to understand a reality. As a process, it shall not be only about method, but also methodology, namely a process of thinking, the brought interest and the achieved value premises. Its guiding question is Ricoeurs theologizing methodology called hermeneutics. Through dialogue with many partners, Ricoeur found a methodology of reality-reading, first affirmative then critical. This is an affirmative-critical gesture. However, this methodology is inadequate to do reading on an extreme context. It takes effort to reverse Ricoeur's methodology by first prioritizing the critical against the reality distortion, and only then be affirmative to uncover hope of a good and just life. Finally, the theologizing process requires a dialectical methodology of reading a reality, between critical-affirmative and affirmative-critical gestures. Context at hand shall determine what goes first.